Teaching Materials Containing Papuan Cultural Wisdom to Develop Children's Story Writing Skills in Class V Elementary Schools - Kasse, Fransiskus; Sudiyanto; Yulisetiani, Septi (Journal of Education Technology, 2024)
Developing teaching materials containing Papuan cultural wisdom is an important step in improving writing skills and overcoming the challenge of low literacy levels of students in Papua. This research aims to develop teaching materials containing Papuan cultural wisdom to improve students' writing skills. This R&D research focuses on developing teaching materials using the 4D model, namely Define, Design, Development and Dissemination.  The subjects in this research were fifth grade elementary school students with a sample of 70 students in the control class and experimental class. Data collection was carried out by observation, interviews, questionnaires and documentation. Data analysis was carried out using interactive analysis techniques, validation and product testing. Apart from that, the data was also analyzed using qualitative descriptive analysis and quantitative analysis. The results of the study showed an increase in the average pretest score in the control class to 67.3, while the experimental class reached 69.5. After the treatment was carried out and ended with the post-test, there was an increase in the average score in the control class to 75.73, and the experimental class 90.28. The higher average increase in post-test scores in the experimental class indicates the potential for increasing students' understanding by using Papuan cultural wisdom teaching materials. Innovation in teaching materials with Papuan cultural wisdom theoretically has implications for complementing and strengthening previous theories regarding teaching materials and story writing skills. Practically, the results of this research can contribute to Papuan cultural wisdom and effectively improve elementary school students' short story writing skills.